Hospital admission flow and nutritional support in a cohort of pediatric patients with COVID-19 - Aline Pereira Queiroz; Caroline dos Santos; Greice Milena Sant'Ana Reis; Paulo Sergio Carvalho Matos; Rogério dos Santos e Santos; Tamires de Jesus Silva
Abstract In view of the current panorama of hospital nutritional care, it is necessary to review nutritional care practices in hospital units, in order to ensure nutritional monitoring and quality of care. Therefore, it is necessary to build flows of nutritional assistance practices at the pediatric hospital level, based on the recommendations of the Federal Council of Nutritionists and the Brazilian Society of Parenteral and Enteral Nutrition, aiming at not generating a deficit in the nutritional monitoring of the patient and in reducing the risk of contamination of the professional. When individual protection equipment is available, nutritional admission will be made in person and during hospitalization, monitoring can be performed using secondary data from electronic medical records and / or telecommunication with the multidisciplinary team. The implementation of nutritional routines in hospitals in times of Covid-19 pandemic generates more assertive conducts for the prevention and treatment of malnutrition and other nutritional implications, also guaranteeing the safety of professionals in assistance in pediatric units..